Factors affecting exhaled nitric oxide measurements: the effect of sex - Williamson Avis J; McLachlan Christene R; Filsell Sue; Hancox Robert J; Greene Justina M; Mandhane Piush; Taylor D Robin; Cowan Jan O; Smith Andrew D; Sears Malcolm R (Respiratory Research, 2007)
Abstract Background Exhaled nitric oxide (FENO) measurements are used as a surrogate marker for eosinophilic airway inflammation. However, many constitutional and environmental factors affect FENO, making it difficult to devise reference values. Our aim was to evaluate the relative importance of factors affecting FENO in a well characterised adult population. Methods Data were obtained from 895 members of the Dunedin Multidisciplinary Health and Development Study at age 32. The effects of sex, height, weight, lung function indices, smoking, atopy, asthma and rhinitis on FENO were explored by unadjusted and adjusted linear regression analyses. Results The effect of sex on FENO was both statistically and clinically significant, with FENO levels approximately 25% less in females. Overall, current smoking reduced FENO up to 50%, but this effect occurred predominantly in those who smoked on the day of the FENO measurement. Atopy increased FENO by 60%. The sex-related differences in FENO remained significant (p < 0.001) after controlling for all other significant factors affecting FENO. Conclusion Even after adjustment, FENO values are significantly different in males and females. The derivation of reference values and the interpretation of FENO in the clinical setting should be stratified by sex. Other common factors such as current smoking and atopy also require to be taken into account.